2011
DOI: 10.1186/1476-072x-10-24
|View full text |Cite
|
Sign up to set email alerts
|

Spatial association of racial/ethnic disparities between late-stage diagnosis and mortality for female breast cancer: where to intervene?

Abstract: BackgroundOver the past twenty years, racial/ethnic disparities between late-stage diagnoses and mortality outcomes have widened due to disproportionate medical benefits that different racial/ethnic groups have received. Few studies to date have examined the spatial relationships of racial/ethnic disparities between breast cancer late-stage diagnosis and mortality as well as the impact of socioeconomic status (SES) on these two disparities at finer geographic scales.MethodsThree methods were implemented to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 39 publications
2
62
0
Order By: Relevance
“…Age and marital status, and distance within three miles radius of MS facilities were statistically significant for advanced breast cancer for Hispanic and White women, but not for Black women (p<0.05). Davidson et al and Tian et al [23,27] found similar results in late-diagnosis of breast cancer for Hispanic women, but not for Asian or White women.…”
Section: Davidson Et Al [23]supporting
confidence: 61%
See 2 more Smart Citations
“…Age and marital status, and distance within three miles radius of MS facilities were statistically significant for advanced breast cancer for Hispanic and White women, but not for Black women (p<0.05). Davidson et al and Tian et al [23,27] found similar results in late-diagnosis of breast cancer for Hispanic women, but not for Asian or White women.…”
Section: Davidson Et Al [23]supporting
confidence: 61%
“…Three studies did not report mean or median age of the study population [27].Two studies compared data in metropolitan suburbs with a higher concentration of minority population [27]. One study comprised a large populace of women in 11 heterogeneous states [18], while another study consisted of several states as part of the Cancer Research Network (Table 1) [33].…”
Section: Socio-demographic Status Of Women and Neighborhood-level Detmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, about 45% of all cancers are diagnosed among those younger than 65 years, and the average length of survival following breast cancer diagnosis has been shown to be substantially lower among low-income people than among those with higher incomes, even in studies that controlled for cancer stage at the time of diagnosis (Tian, Wilson, & Zhan, 2011;Freeman, Ricardo, Campbell, Barrett, & Warnecke, 2011). About 60% of adult Medicaid enrollees have a chronic or disabling condition (Boyd et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…For example, breast cancer is more common in higher socio-economic classes and among women whereas lung cancer is more common in lower classes and mainly among men who smoke . On the other hand, cancers do not generally show such a strong relation to social classes as cardiovascular diseases (Hiatt and Breen, 2008;Tian et al, 2011) .…”
Section: Theoretical Aspects Of Cancer Incidencementioning
confidence: 99%